Monogeneans of West African cichlid fish: evolution and cophylogenetic interactions - Mendlová, Monika; Desdevises, Yves; Civáňová, Kristína; Pariselle, Antoine; Šimková, Andrea (PloS one, 2012)
The goals of this paper were to investigate phylogenetic and evolutionary patterns of cichlid fish from West Africa and their Cichlidogyrus and Scutogyrus monogenean parasites, to uncover the presence of host-parasite cospeciation and to assess the level of morphological adaptation in parasites. This required the following steps, each one representing specific objectives of this paper: (1) to build phylogenetic trees for Cichlidogyrus and Scutogyrus species based on ribosomal DNA sequences, (2) to investigate phylogenetic relationships within West African cichlid fish based on the analysis of mitochondrial cytochrome b DNA sequences, (3) to investigate host-parasite cophylogenetic history to gain clues on parasite speciation process, and (4) to investigate the link between the morphology of the attachment apparatus and parasite phylogeny. Phylogenetic analyses supported the monophyletic origin of the Cichlidogyrus/Scutogyrus group, and suggested that Cichlidogyrus is polyphyletic and that Scutogyrus is monophyletic. The phylogeny of Cichlidae supported the separation of mouthbrooders and substrate-brooders and is consistent with the hypothesis that the mouthbrooding behavior of Oreochromis and Sarotherodon evolved from substrate-brooding behavior. The mapping of morphological characters of the haptor onto the parasite phylogenetic tree suggests that the attachment organ has evolved from a very simple form to a more complex one. The cophylogenetic analyses indicated a significant fit between trees using distance-based tests, but no significant cospeciation signal using tree-based tests, suggesting the presence of parasite duplications and host switches on related host species. This shed some light on the diversification process of Cichlidogyrus species parasitizing West African cichlids.
Keywords: DNA, Ribosomal; Animals; Cichlids; interakce hostitele a parazita; Phylogeny; cichlidy; Platyhelminths; Host-Parasite Interactions; Biological Evolution; fylogeneze; biologická evoluce; ribozomální DNA; ploštěnci; zvířata